Evaluation of ischemia-modified albumin level and parameters related with oxidative stress in early onset androgenetic alopecia - Nazik, Hulya; Nazik, Selcuk; Kiraz, Zeynep Kusku; Gul, Feride Coban; Demir, Betul (Turkish Soc Dermatology Venerology, 2017)
Background and Design: Ischemia-modified albumin (IMA) is a biomarker, which is an indicator of ischemia and oxidative stress, and measured by the albumin cobalt binding test. Androgenetic alopecia (AGA) is the most important cause of hair loss in males. Hair loss that is affected by androgenic hormones, age, and ethnic, family and environmental factors, may lead to psychological, social and physical problems in some individuals. The aim of the present study was to investigate the factors affecting AGA, and the correlation between AGA and IMA. Materials and Methods: Fifty male patients with AGA aged 18-35 years and 30 males of similar age without AGA were included in the study. Patients with AGA stage 3 or higher were included in the study group. Blood samples were collected after a 12-hour fasting period. Blood glucose, total cholesterol, high-density lipoprotein (HDL), low-density lipoprotein (LDL), triglyceride, insulin, testosterone, dehydroepiandrosterone-sulfate (DHEA-S), and albumin levels were analyzed using an autoanalyzer. IMA values were evaluated using a MINDRAY BS 2000 autoanalyzer. Results: A total of 80 individuals were included in the study. There was no significant difference in mean age (p=0.179), body mass index (p=0.847), DHEA-S (p=0.247), testosterone (p=0.874), lipid profile [triglyceride (p=0.086), total cholesterol (p=0.492), HDL (p=0.993), LDL (p=0.544)], insulin resistance (p=0.399) and IMA (p=0.976) between study group and control group. Additionally, a family history of alopecia was found to be significantly higher in the study group (p=0.000). Moreover, there was a positive correlation between AGA grade and insulin resistance (r=0.296; p=0.037). Conclusion: AGA, which leads to many cosmetic and psychosocial problems, was more frequent in individuals with a family history of alopecia; also, there was a positive correlation between AGA stage and insulin resistance. On the other hand, there was no significant correlation between AGA and IMA.
Keywords: Ischemia-modified albumin; androgenetic alopecia; insulin resistance